Probiotic Effects of Lactobacillus fermentum ZJUIDS06 and Lactobacillus plantarum ZY08 on Hypercholesteremic Golden Hamsters - Yang, Dongting; Lyu, Wentao; Hu, Ziyi; Gao, Jiting; Zheng, Zhiyao; Wang, Weijun; Firrman, Jenni; Ren, Daxi (Frontiers in Nutrition, 2021)
This study aimed to evaluate the probiotic effects of Lactobacillus fermentum ZJUIDS06 and Lactobacillus plantarum ZY08 on hyperlipidemic golden hamsters. A hyperlipidemic model was established via high cholesterol diet in golden hamsters, after which lyophilized Lactobacillus fermentum ZJUIDS06 and Lactobacillus plantarum ZY08 were orally administered individually for 8 weeks. The physiological characteristics of golden hamsters and short chain fatty acid (SCFA) in the colon were assessed by automatic Biochemical Analyzer and gas choromatograph, respectively. A MiSeq sequencing-based analysis of the bacterial 16S rRNA gene (V3–V4 region) in the cecum content was performed to analyze the cecum microbiota. Correlations between sets of these variables were also investigated using the R package “corrplot”. Results showed that neither Lactobacillus fermentum ZJUIDS06 nor Lactobacillus plantarum ZY08 inhibited body weight increase. However, supplementation with Lactobacillus fermentum ZJUIDS06 for 8 weeks increased colon short chain fatty acid levels (P < 0.05), decreased serum low-density lipoprotein, total cholesterol, and triglycerides levels, and also induced changes in the cecum microbiota of hyperlipidemic golden hamsters. Remarkably, oral delivery of Lactobacillus fermentum ZJUIDS06 increased the relative abundance of Parabacteroides in the cecum, which served as a biomarker for colon SCFA production and improvement of serum cholesterol levels. In a word, Lactobacillus fermentum ZJUIDS06 improved hyperlipidemia in golden hamsters, which correlated to an increase inshort chain fatty acid levels and relative abundance of Parabacteroides, indicating its potential use in functional foods that can help lower cholesterol.